A simple panel-CADF test for unit roots - Mauro Costantini; Claudio Lupi (Institute for Advanced Studies (IHS), 2011)
In this paper we propose a simple extension to the panel case of the covariate-augmented Dickey Fuller (CADF) test for unit roots developed in Hansen (1995). The extension we propose is based on a p-values combination approach that takes into account cross-section dependence. We show that the test is easy to compute, has good size properties and gives power gains with respect to other popular panel approaches. A procedure to compute the asymptotic p-values of Hansen's CADF test is also a side-contribution of the paper. We also complement Hansen (1995) and Caporale and Pittis (1999) with some new theoretical results. Two empirical applications are carried out for illustration purposes on international data to test the PPP hypothesis and the presence of a unit root in international industrial production indices.
Keywords: C22; C23; F31; 330; unit root; panel data; approximate P-values; Monte Carlo